2012
DOI: 10.1007/10_2012_156
|View full text |Cite
|
Sign up to set email alerts
|

Engineered MSCs from Patient-Specific iPS Cells

Abstract: Mesenchymal stroma/stem cells (MSCs) represent a heterogenic cell population that can be isolated from various tissues of the body or can be generated from pluripotent stem cells by in vitro differentiation. Various promising pre-clinical and clinical studies suggest that MSCs might stimulate endogenous regeneration and/or act as anti-inflammatory agents, which could be of high therapeutic relevance for a number of diseases, including graft-versus-host disease after allogeneic hematopoietic stem cell transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…Because mesenchymal cells are essential for functional and durable vessel formation, deriving them from clinically accessible precursors, such as hiPS cells, would be a critical step for the translation of this tissue-engineered vessel approach in patients (28). To test the possible use of mesenchymal cells derived from hiPS cells in the engineered vessel model, we isolated CD73 + cells from the CD31 − CD144 − fraction of differentiated HS27-iPS cells and expanded them in human mesenchymal stem cell (MSC) medium for a period of 2 wk (SI Appendix, SI Materials and Methods).…”
Section: Mesenchymal Cells Derived From Hips Cells Can Support Hips-ec-mentioning
confidence: 99%
“…Because mesenchymal cells are essential for functional and durable vessel formation, deriving them from clinically accessible precursors, such as hiPS cells, would be a critical step for the translation of this tissue-engineered vessel approach in patients (28). To test the possible use of mesenchymal cells derived from hiPS cells in the engineered vessel model, we isolated CD73 + cells from the CD31 − CD144 − fraction of differentiated HS27-iPS cells and expanded them in human mesenchymal stem cell (MSC) medium for a period of 2 wk (SI Appendix, SI Materials and Methods).…”
Section: Mesenchymal Cells Derived From Hips Cells Can Support Hips-ec-mentioning
confidence: 99%
“…During allogeneic cell or organ transplantation, cytotoxic and helper T-lymphocytes get activated and kill the targeted cells or promote rejection of the transplanted organ [ 46 ]. Because MSCs can secrete anti-inflammatory molecules to dampen inflammatory reaction [ 47 ], one can speculate that iPSC-derived MSCs could also provide a valuable cell source for immunomodulatory therapies (for review see [ 11 ]). In order to investigate the immunomodulatory properties of iPSC-MSCs we have used Mixed Lymphocyte Reaction (MLR) to mimic inflammatory reaction by mixing CD4 + lymphocytes with healthy donor peripheral blood mononuclear cells (PMNCs) on iPSC-MSCs and BM-MSCs feeder layers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In principal, such needs would be met by pluripotent stem cells exhibiting an unlimited proliferation capacity and that can be generated from patients' samples via reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) [ 7 10 ]. Such human iPSCs are responsive to differentiation stimuli during in vitro cultivation and in the recent past the generation of iPSC-derived MSCs (iPSC-MSCs) was described and it was demonstrated that iPSC-MSCs displayed comparable antigen profile and differentiation capability to bone marrow MSCs (BM-MSCs) and exhibited considerable functional properties [ 11 16 ]. Moreover, there is convincing evidence that iPSC-MSCs with higher expansion capacities can be transplanted in many degenerative diseases resulting in similar outcomes as BM-MSCs [ 13 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs) are pluripotent cells derived from terminally differentiated cells by dedifferentiation. The generation of iPSCs creates the possibility of generating tissue-specific cells, including HSCs [63][64][65][66][67][68] or MSCs [69][70][71][72][73][74][75][76], but further study is required before clinical application of iPSCs can commence. Taken together, immune reconstruction and modification of genetic predisposition of hematopoietic stem cells are important for radical cure of IBD.…”
Section: Intestinal Stem Cells and Other Stem Cells In Ibdmentioning
confidence: 99%